Pediatric Neutropenic Patients Care in Turkey - (:unkn) unknown (AVES YAYINCILIK, IBRAHIM KARA, 2019)
Objective: Infection is a common complication in children with malignancies. There is no consistent guidance for environmental infection control and isolation precautions for neutropenic patients (NP). There are differences between centers. The aim of this questionnaire study was to determine these differences in Turkey. Material and Methods: A multicenter-descriptive questionnaire was conducted on 36 centers from different geografical locations of Turkey. Bone marrow transplantation units were excluded. Each center was contacted at least three-times. Questionnaire was answered by two different doctors from each center. Results: Thirty-six centers including 20 (55.5%) University Hospitals, 12 (%33.3) Research Hospitals, three (8.3%) State Hospital and one Private University Hospital participated in this survey. 94.3% of the centers had a bed capacity of 50 beds and over. Twenty-one (58.3%) centers had pediatric infection ward that followed febrile NP. All centers had an infection control committee. 25% (9/36) of the centers always followed pediatric neutropenic fever patients in a single room. 66.6% (24/36) of the centers had toilet in all patients' room. The door features of patients' room included mostly (94.1%, 32/34) manually opened door. Ten (27.7%) centers had hepa filter system, five of them had positive-negative pressure room. Thirteen (38.2%, 13/34) centers prefered hickmann catheter for accessing a patient's central line. Training was given for catheteter care in all centers. Sixteen (44.4%) centers had determined policies about keeping toys in patient rooms. Visitor restrictions were performed in all centers. None of the centers allowed plants or flowers in hospital rooms. There was a neutropenic diet specific for pediatric NP provided in twenty-seven centers (75%). Conclusion: The prevention and control of infection contributes to the improvement of the prognosis of patients with hematological malignancies. Physicians must be aware of the infection risks and take precautions for infectious complications through the neutropenic period and standard protocols should be established and implemented for patients with hematological malignancies.
Keywords: Neutropenic patients; children; infection control